2003
DOI: 10.1007/s00223-003-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects on RANK Ligand and Osteoprotegerin in Osteoporosis and Vascular Disease

Abstract: The clinical coincidence of osteoporosis and vascular disease has long indicated that common mediators may adversely affect bone metabolism and vascular integrity alike. Receptor activator of NF-kappaB ligand (RANKL) is an important cytokine for bone resorption that acts through its osteoclastic receptor, receptor activator of NF-kappaB (RANK), while osteoprotegerin serves as a decoy receptor that binds RANKL and prevents activation of RANK. Skeletal and vascular cells are sources and targets of RANKL and OPG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 24 publications
3
83
0
10
Order By: Relevance
“…The strong positive relation we found between age and OPG was previously described in men (17,26,27), elderly women (15,23), and diabetic subjects (27) and has been interpreted as a compensatory mechanism counteracting the age progression of bone resorption and atherosclerosis (16,17,19,28). This increase was also linked to the expected modifications in renal function observed with age.…”
Section: Discussionsupporting
confidence: 81%
“…The strong positive relation we found between age and OPG was previously described in men (17,26,27), elderly women (15,23), and diabetic subjects (27) and has been interpreted as a compensatory mechanism counteracting the age progression of bone resorption and atherosclerosis (16,17,19,28). This increase was also linked to the expected modifications in renal function observed with age.…”
Section: Discussionsupporting
confidence: 81%
“…In general, serum RANKL levels appear unaltered, although they have sometimes declined as serum OPG levels increased. 20,21,43 Furthermore, in a recent study, Kiechl et al showed in a large scale epidemiological study that serum RANKL levels did not correlate with atherosclerosis, but baseline RANKL levels were shown to be a predictor of vascular risk. 44 Thus, the role of serum RANKL levels as predictors of cardiovascular risk is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical coincidence of osteoporosis and vascular disease has long indicated that common mediators may adversely affect both bone metabolism and vascular integrity (14). Osteoprotegerin binds to RANKL and tumor necrosis factor-related apoptosis-inducing ligand (15), thereby inhibiting the ligation of these mediators to their receptors and inhibiting their subsequent activation of specific proinflammatory and proapoptotic signaling pathways (16).…”
Section: Discussionmentioning
confidence: 99%